An Investigation of the Integration of Inter-semiotic Complementarity in Iraqi EFL Textbook - Riyadh Sarhan Jabour; Wafaa Mokhlos Faisal (Register Journal, 2022)
Nowadays, multimodal texts are widely used in the media, schools, and daily life. There have been several studies on nonverbal semiotics in multi-semiotic texts. This study examines the complementarity of verbal and visual semiotic modes in an Iraqi EFL textbook. Royce's (2007) inter-semiotic complementarity and (Kress,van Leeuwen's 1996) structure of information value were used to analyse an Iraqi EFL textbook titled English for Iraq (Garnet, 2017). According to the analysis, the entire textbook is not built on a page-by-page path that allows linear and nonlinear reading. Although the information layout varies from page to page, the overall structure of the textbook image allows for a linear reading path from start to finish. Texts in multimodal EFL are required. This study investigated the relationship between verbal text and image in terms of address, social distance, and participation because multimodality conveys teachers' perspectives on language learning (the extent to which the reader engages with what is represented). This study's sample includes analytical units. Each verbal and visual sample text-image relationship was determined, and the participation and address levels were comparable. We discovered that social distance favors divergence over convergence in English education and learning. Young students select, design, and employ multimodal textbook materials.Keywords: Multimodality, inter-semiotic complementarity, semiotics’ mode, EFL, School textbooks